Confronting climate uncertainty in water resources planning and project design : the decision tree framework - Ray, Patrick A.; Brown, Casey (Water-supply engineer) (World Bank Group, 2015)
The Decision Tree Framework is a decision support tool that aims to help project managers and development practitioners to pragmatically assess potential climate risks. This document, developed by the Water Global Practice with the support of our Water Partnership Program (WPP), helps practitioners navigate the maze of existing climate assessment methods and models. The tool first screens for climate vulnerabilities, and a "decision tree" subsequently helps project teams assess and then develop plans to manage climate and other risks. It uses a step-by-step design--similar to a tree on which each "branch" builds off the previous one. [Foreword]--